The relationship between remote work and job satisfaction: The mediating roles of social interaction and work-family conflict - Sasho Blazhevski; Ivona Mileva; Marjan Bojadjiev (University American College Skopje, 2021)
The global pandemic, COVID-19, has prevented much of the workforce from traveling to work to reduce the spread of the virus. This has resulted in employers and employees looking for alternative work arrangements, thus nowadays, remote working "enjoys" its momentum that is spreading more and more into the business practice. The remote work is considered to have a significant relation with job satisfaction; therefore, it has an impact on organizational efficacy and success. Yet,the new way of functioning arises questions on social interaction and work-family conflict. More specifically, remote working can result in physical and mental health issues, through the decreased level social interaction and work-family conflicts that have impact on the level of job satisfaction. The goal of this study is to explore the relationship between remote work and job satisfaction with focus on mediating role of social interaction and work-family conflict. In other words, the study examines the factors that affect the job satisfaction while working remotely and the changes that can be made in people's homes in order to provide them a sense of working atmosphere. Both aspects are of special importance because they can serve as a reference for designing ideas and changes in homes for the purpose of creating better working conditions.
Keywords: 330; COVID-19; remote work; job satisfaction; social interaction; work-family conflict